2012
DOI: 10.3389/fneur.2012.00062
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Neurobehavioral Impairment from Sleep Deprivation in Older Adults: Contribution of Adenosinergic Mechanisms

Abstract: A night without sleep is followed by enhanced sleepiness, increased low-frequency activity in the waking EEG, and reduced vigilant attention. The magnitude of these changes is highly variable among healthy individuals. Findings in young men of low and high subjective caffeine sensitivity suggest that adenosinergic mechanisms contribute to inter-individual differences in sleep deprivation-induced changes in EEG theta activity, as well as optimal performance on the psychomotor vigilance task (PVT). In comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
26
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 70 publications
7
26
1
Order By: Relevance
“…Synaptic release of norepinephrine activates astrocytic α 2 -adrenoreceptors, which triggers the extracellular release of ATP, that is then hydrolyzed to adenosine (196, 219, 220). The adenosine binds to presynaptic A1Rs and induces hyperpolarization by inactivating Ca 2+ inward channels and activating K + channels (196, 221). Studies employing SHRs observed increased A1R expression in the NTS (194, 222), with enhanced sensitivity to adenosine (222) that blunted BRS resulting in a hypertensive state (193, 196, 223, 224).…”
Section: Diverse Models Of Hypertension Demonstrate Electrophysiologimentioning
confidence: 99%
“…Synaptic release of norepinephrine activates astrocytic α 2 -adrenoreceptors, which triggers the extracellular release of ATP, that is then hydrolyzed to adenosine (196, 219, 220). The adenosine binds to presynaptic A1Rs and induces hyperpolarization by inactivating Ca 2+ inward channels and activating K + channels (196, 221). Studies employing SHRs observed increased A1R expression in the NTS (194, 222), with enhanced sensitivity to adenosine (222) that blunted BRS resulting in a hypertensive state (193, 196, 223, 224).…”
Section: Diverse Models Of Hypertension Demonstrate Electrophysiologimentioning
confidence: 99%
“…Raw data were available for all studies except study V4, for which group-average data were captured from a published figure. 8 …”
Section: Datasetsmentioning
confidence: 99%
“…Subjects received a capsule with either placebo after 11 and 23 h of wakefulness (at 19:00 and 07:00, respectively) or 200 mg of caffeine on each of the two occasions. 8,15 The TSD phase was preceded by 2 nights of 8 h TIB (baseline) and followed by 1 night of 10.5 h TIB (recovery). During the TSD phase, subjects completed 14 sessions of a 10-min PVT at 3-h intervals.…”
mentioning
confidence: 99%
“…On the other hand, it was recently shown that the process of normal aging can bring some advantages to older people living in modern 24-hour societies. For instance, they may better tolerate sleep deprivation compared to younger people [30][31][32][33]. It seems that research into ageassociated changes in principal component structure of the wake and sleep EEG signal can provide deeper insights into the regulatory processes underlying optimal sleep of older people, and their predisposition to both certain sleep disturbances and advantageous waking ability.…”
Section: Discussionmentioning
confidence: 99%